2023
DOI: 10.1159/000530932
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Exposure to a Healthy Weight Body Is a Promising Adjunct Treatment for Anorexia Nervosa

Abstract: <b><i>Introduction/Objective:</i></b> Treatment results of anorexia nervosa (AN) are modest, with fear of weight gain being a strong predictor of treatment outcome and relapse. Here, we present a virtual reality (VR) setup for exposure to healthy weight and evaluate its potential as an adjunct treatment for AN. <b><i>Methods:</i></b> In two studies, we investigate VR experience and clinical effects of VR exposure to higher weight in 20 women with high weight conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Furthermore, the inability to update their body image based on new experiences hinders them from accurately interpreting their internal signals related to emotions. To address this issue, as done with anxiety disorders, VR/AR systems are successfully used to extinguish/habituate craving [ 50 ] and anxiety responses to food‐related [ 51 , 52 ] and body-related cues [ 53 , 54 ].…”
Section: Metaverse Applications In Mental Disorders: the First Evidencementioning
confidence: 99%
“…Furthermore, the inability to update their body image based on new experiences hinders them from accurately interpreting their internal signals related to emotions. To address this issue, as done with anxiety disorders, VR/AR systems are successfully used to extinguish/habituate craving [ 50 ] and anxiety responses to food‐related [ 51 , 52 ] and body-related cues [ 53 , 54 ].…”
Section: Metaverse Applications In Mental Disorders: the First Evidencementioning
confidence: 99%
“…To illustrate this, we surveyed all 2022 and 2023 issues of Psychotherapy and Psychosomatics which ranks among the highest-impact psychology journals (Impact Factor 2023: 26.617). We found that of 17 studies that reported results of regression analyses [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], only six made use of at least one of these visualizations [22][23][24][25][26][27]. One of them applied a forest plot variant [22].…”
Section: Reporting and Visualizing Regression Modelsmentioning
confidence: 99%
“…Consequently, 81 papers were deemed eligible for a full text review; 71 of them being excluded for various reasons (see Supplementary File S3). A total of 10 publications were finally included [116][117][118][119][120][121][122][123][124][125]. The Cohen kappa coefficient demonstrated a substantial level of agreement, being categorized as "good" (κ = 0.67) (range 0.61-0.80) based on the categories developed by Altman [44].…”
Section: Study Selection and Inclusionmentioning
confidence: 99%
“…The majority of the studies were conducted in Spain (n = 5; 50%) [117,118,[121][122][123]. The remaining papers were published in Italy (n = 3; 30%) [120,124,125], Germany (n = 1; 10%) [116] and the Netherlands (n = 1; 10%) [119]. All the studies involved followed a quantitative approach (n = 10; 100%) [116][117][118][119][120][121][122][123][124][125] (Table 1).…”
Section: General Characteristics Of the Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation